Bird-watching guide’s English module for promoting Balinese nature and culture - Dika Pranadwipa Koeswiryono; Francisca Titing Koerniawaty (Politeknik Negeri Bali, 2018)
There has been a discrepancy between visitors needs of guide service at a bird-watching site in Bali and the guides English competence. This article addresses the language learning needs of the guides and how they are analyzed to construct an English module for the bird-watching guides. The module can hopefully improve the guiding service, enhance the tourists’ experience and contribute to the conservation of culture via tourism activities. Observation and interview with 5 officers of the bird village and observations on the village’s vicinity revealed their necessities, lack and want in terms of English learning, in relation to their occupation as guides. Beside knowledge about the heron population, the material also covers insight about Balinese’s traditional house, their prayer offerings, and their spiritual philosophy. Each chapter of the module encloses conversation and role-play, grammar focus, pronunciation drill, and reading section. The English material was then judged by the experts in language teaching and in Hinduism.